2015
DOI: 10.3899/jrheum.150280
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like Growth Factor 1 and Adiponectin and Associations with Muscle Deficits, Disease Characteristics, and Treatments in Rheumatoid Arthritis

Abstract: Objective Rheumatoid arthritis (RA) is associated with low muscle mass and density. The objective of our study was to evaluate associations between 2 serum biomarkers [insulin-like growth factor 1 (IGF-1) and adiponectin] and skeletal muscle in RA. Methods Whole-body dual energy X-ray absorptiometry measures of the appendicular lean mass index (ALMI; kg/m2) and total fat mass index (kg/m2), as well as the peripheral quantitative computed tomography measures of the lower leg muscle and fat cross-sectional are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 41 publications
1
19
1
Order By: Relevance
“…This reduction was significantly elevated in treated group with S.O or both doses of MTX. These results were in accordance with Baker et al, (2016) who found lower IGF-1 levels in RA patients with greater disease activity and severity. In the current study, MTX therapy caused deterioration in liver function as there was a significant elevation in liver enzymes and total billirubin serum levels accompanied with significant deplelion in the serum total protein.…”
Section: ‫ـــــــــــــــــــــــــــــــــــــــــــــــــــ‬ ‫ـــــsupporting
confidence: 92%
“…This reduction was significantly elevated in treated group with S.O or both doses of MTX. These results were in accordance with Baker et al, (2016) who found lower IGF-1 levels in RA patients with greater disease activity and severity. In the current study, MTX therapy caused deterioration in liver function as there was a significant elevation in liver enzymes and total billirubin serum levels accompanied with significant deplelion in the serum total protein.…”
Section: ‫ـــــــــــــــــــــــــــــــــــــــــــــــــــ‬ ‫ـــــsupporting
confidence: 92%
“…Local overexpression of IGF-1 has successfully rescued muscles in various chronic and experimental muscle atrophy models including Dex injected rats [ 115 ], age-related muscle atrophy [ 113 ], hindlimb suspension [ 156 ], and Ang II infusion in rodents [ 39 , 74 , 76 ], as well as in the mouse models of ALS [ 157 ] and muscular dystrophy [ 158 , 159 , 160 ]. Rheumatoid arthritis (RA) is associated with low muscle mass and density, and skeletal muscle of RA patients have been shown to have lower levels of IGF-1, which were associated with the severity of the disease, low appendicular lean mass, and lower myofiber CSA [ 161 ]. In a rat RA model, both circulating and skeletal muscle IGF-1 were decreased, the animals showed lower muscle mass, and subcutaneous injection of IGF-1 (100 µg/kg; twice daily for 12 days) increased body and hindlimb muscle weight without changing arthritis.…”
Section: Igf-1 Changes In Chronic Conditions and Aging-associatedmentioning
confidence: 99%
“…We previously demonstrated associations between adiponectin and evidence of cachexia in RA (40). The novel associations between adiponectin and bone outcomes observed in this RA cohort were independent of body composition.…”
Section: Discussionmentioning
confidence: 97%